2021
DOI: 10.3390/diagnostics11101752
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Magnetic Resonance in Peripartum Cardiomyopathy: Comparison with Idiopathic Dilated Cardiomyopathy

Abstract: Background: Peripartum (PPCM) and dilated (DCM) cardiomyopathies are distinct forms of cardiac disease that share certain aspects in clinical presentation. Aim: We hypothesized that different cardiac structural changes underlie PPCM and DCM, and we aimed to investigate them with cardiovascular magnetic resonance (CMR). Methods: We included 21 PPCM patients (30.5 ± 5.9 years) and 30 female DCM patients (41.5 ± 16.8 years) matched for left ventricular ejection fraction. Biventricular and biatrial volumetric and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…PPCM's initial presentation is often acute. Therefore, there are frequently no or limited areas of fibrosis detected in CMRI [28]. This partially elucidates the ability of the heart muscle to recover.…”
Section: Extracellular Matrixmentioning
confidence: 94%
“…PPCM's initial presentation is often acute. Therefore, there are frequently no or limited areas of fibrosis detected in CMRI [28]. This partially elucidates the ability of the heart muscle to recover.…”
Section: Extracellular Matrixmentioning
confidence: 94%
“…Prior CMR studies have shown that there is a high prevalence of myocardial oedema, fibrosis [as shown with late gadolinium enhancement (LGE)], regional wall motion abnormalities and pericardial effusion at the time of diagnosis [67]. Prevalence of LGE in previous studies on PPCM ranged between 13 and 71% [67,68 ▪▪ ,69 ▪▪ ,70]. LGE distribution typically has a nonischemic pattern.…”
Section: Clinical Presentation Of Peripartum Cardiomyopathymentioning
confidence: 99%